Pengaruh Promosi Kualitas Pelayanan Kualitas Produk Dan Harga Terhadap Keputusan Pembelian ( Distro Dishcaven) - Edi Ardiansyah; Muhammad Mansur; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This research was conducted at Distro Distro, Jl. Ranugrati no 25 Sawojajar. Malang city. The type of research used is explanatory research with a quantitative approach. The purpose of this study was to determine the effect of promotion, service quality, product quality and price on purchasing decisions. The independent variables used are promotion, service quality, product quality and price, while the dependent variable is purchasing decisions. The sample used in this study were 95 respondents who were consumers aged 15-30 years, the local community of Malang City who settled or temporarily and consumers who had made a purchase. Data collection techniques using questionnaires. The analytical method used is instrument test, multiple linear regression analysis, classical assumption test, determination test, f test and t test using SPSS 16.0 computer software for data processing. The results of this study indicate that promotion affects purchasing decisions, service quality affects purchasing decisions, product quality affects purchasing decisions and price affects purchasing decisions. Promotion, service quality, product quality and price simultaneously affect purchasing decisions. Keywords: Promotion, Service Quality, Product Quality,